High-Performance Control Simulation of PFC Converter for Electric Vehicle Charger - Bubo Zhu; Shaojie Sun; Yongfeng Jia (Journal of Control Science and Engineering, 2023)
In order to solve the problems of low power factor and large harmonic pollution of some electrical equipment connected to the power grid, such as electric vehicle charger system, the author proposes a high-performance control simulation study of a PFC converter for electric vehicle charger. Using the staggered parallel boost power factor correction circuit topology of electric vehicle chargers as the front stage, its high power factor and low harmonic current characteristics can reduce the pollution to the power grid, and the detailed design process and loss analysis of the circuit are given. Through the digital control method and hardware optimization design, the loss is reduced, and the conversion efficiency of the power factor correction converter in the full power range is high, which meets the efficiency requirements of the platinum version and achieves the goal of energy saving and environmental protection. The test results show that the actual efficiency of the experimental prototype is 97.43%, 97.55%, and 97.36%, which are far higher than the efficiency requirements of the platinum version. Conclusion. The high-performance control of the PFC converter of the electric vehicle charger has certain guiding significance for the application in the electric vehicle.